Early career teachers’ social and emotional competencies, self-efficacy and burnout: a mediation model - Ivana Pikić Jugović; Iris Marušić; Jelena Matić Bojić (BMC Psychology)
Abstract Teacher well-being has increasingly become a prominent research topic due to its significant impact on various teacher and student outcomes. This focus is particularly crucial for early career teachers, who often encounter numerous challenges at the beginning of their careers, leading to elevated levels of stress and burnout. Our study aimed to examine the relationship between social and emotional competencies and burnout of early career teachers and the potential mediating role of teacher self-efficacy in this relationship. A total of 657 Croatian subject teachers with up to 5 years of experience participated in the study. Structural equation modelling was implemented to test models of hypothesised relations for the overall burnout as a dependent variable and for each burnout dimension: exhaustion, mental distance, cognitive impairment, and emotional impairment. Tested models singled out self-management and social awareness as two social and emotional competencies that are, along with teacher self-efficacy, particularly predictive of burnout. Self-management predicted lower overall burnout and teacher self-efficacy partially mediated this relationship. Social awareness also predicted lower burnout in teachers, but this relationship was fully mediated by teacher self-efficacy. Early career teachers who are better at managing and motivating themselves, who are socially aware and behave more prosocially were feeling more efficacious as teachers and, subsequently, displayed fewer symptoms of burnout. At the level of burnout dimensions, the overall pattern of relations was mainly retained, indicating that self-management and social awareness are particularly predictive of the four burnout dimensions and that self-efficacy plays a mediating role, either partially or fully, in this relationship. Our findings are especially important in light of the knowledge about early years in teaching being a critical period for teacher career development. They suggest that new teachers could benefit from well-structured mentoring and induction programs designed to ease their transition into schools and foster their well-being in the initial years of teaching.